MEMBANGUN PEMAHAMAN KONSEP SISWA MELALUI MODEL PROBLEM BASED LEARNING - Wardani, Imas Srinana; Sulistyawati, Ida (LPPM Universitas Bina Bangsa, 2023)
The concept of digestive organs is difficult for elementary school (SD) students to understand, so in the learning process a learning model is used. The problem-based learning model is used to build understanding of students' concepts, because this model uses contextual problems that can help students identify elements of concepts. The purpose of this study is to determine the improvement of students' understanding of concepts through problem-based learning models. This type of research is quantitative research with a nonequivalent control group design. The subject of research for grade V elementary school students at SDN Tenggilis Mejoyo I Surabaya. The instrument used is a test of understanding the concept of digestive organs. The results of the analysis can be seen the results of the t test using Mann Whitney the results are significant, the calculation of the test is different from the test score data p-value value < α = 0.05 which means that learning using a problem-based learning model can build understanding of concepts